Energy localization, Fano resonances, and nonlinear meta-optics: Распространение волн в неоднородных системах - Kivshar, Yuri (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
This paper reflects on some memories of the research topics developed at Department No. 29 of the Institute for Low Temperature Physics and Engineering in Kharkov more than 30 years ago. It also provides some recent advances on my major research activities related to those topics, including energy localization and solitons in nonlinear lattices, Fano resonances in photonics and phononics, and nonlinear effects in meta-optics and nanophotonics. Curiously enough, each of those topics can be associated with some memories and discussions that happened in Kharkov long time ago.